Asuhan Keperawatan Stroke Non-Hemoragik pada Ny. R dengan Diagnosa Keperawatan Utama Hambatan Mobilitas Fisik di Ruang Edelweis Atas RSUD Kardinah Kota Tegal - Farhan Fawwaz; Made Suandika (Jurnal Sehat Mandiri, 2023)
Non-hemorrhagic stroke is a clinical sign of dysfunction or damage to brain tissue due to lack of blood flow to the brain so that brain tissue becomes disrupted. The symptoms felt by the patient are the inability to move the left extremity resulting in barriers to physical mobility. Purpose: to describe Nursing Care of Non-Hemorrhagic Stroke in Mrs.R with the Main Nursing Diagnosis of Physical Mobility Barriers in the Edelweiss Room of Kardinah Hospital, Tegal. Data collected on 6 – 8 December 2022. Data collection techniques with anamnesis, physical examination, documentation, observation and interviews. The interventions carried out to overcome barriers to physical mobility is Range Of Motion (ROM) exercises, namely exercises to move body parts to maintain flexibility and joint motion ability carried out for 3x24 hours, there is an increase in muscle strength in the right extremity 2 to 4. The patient's family can do Range Of Motion exercises regularly, so that muscles and joints are not difficult to move. The resultss howed that the provision of Range Of Motion exercise interventions had an effect on increasing the ability to move joints. Conclusion The results of an evaluation carried out for 3 days of impaired physical mobility associated with neuromuscular disorders showed that the problem had been resolved. Suggestions are that patients can do Range Of Motion exercises regularly, so that muscles and joints are not difficult to move.